MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER - Aulia Afza (Ta'dib, 2018)
This research aims at improving students’ activity and learning outcomes through Cooperative Learning Type Numbered Head Together (NHT) in Basic Natural Sciences subject at Program Studi Pendidikan Biologi STKIP PGRI West Sumatera. This research is a classroom action research lasting for 2 cycles. Each cycle consisted of 4 stages, namely planning, implementation, observation, and reflection. The research was conducted in Basic Natural Science class attended by 30 students. The research parameters were the students’ activity identified through the observation sheet recorded the students’ action during the learning process and their learning outcomes gained from a test. Data analysis used percentage formula. The results show that the average of students’ activity on the first cycle was 76.12 and increased in cycle II to 79.45. Meanwhile the students’ learning outcomes in the first cycle was 77.62 with the classical completeness of 73.33% . It increased in cycle II to 78.97 with the classical completeness of 77.33%. In short, the application of cooperative learning model type Numbered Head Together can increase the students’ activity and learning outcomes in Basic Natural Science subject.